Evaluasi Kualitas Sensori Tiga Jenis Tempe yang Beredar di Pasaran dengan Menggunakan Metode Hedonik dan CATA: Sensory Quality Evaluation of Three Types of Tempe Available in the Market Using Hedonic and CATA Methods - Rahmi Naily Maghfiroh; Dimas Wahyu Ekawananto; Made Astawan; Saraswati Saraswati; Tutik Wresdiyati; Wanida Tewaruth Chitisankul; Andi Early Febrinda; Songsak Wattanachaisaereekul (Amerta Nutrition, 2025)
Background: Tempe is a traditional Indonesian fermented soybean product that serves as a source of protein and is recognized in the national and international markets. The variety of tempe quality available on the market is greatly influenced by the facilities and production standards of each business unit. Until now, most tempe producers still use traditional methods and do not apply good hygienic practices. Consequently, adversely affects the quality and market value of their products. Objectives: To evaluate the sensory quality of three types of tempe available in the market, namely tempe for the international market (export), the national market (Indonesia), and the local market (Bogor). Methods: This study used a Completely Randomized Design. Sensory evaluation was conducted using the hedonic and Check-All-That-Apply (CATA) involving 73 consumer panelists. The data will be statistically analyzed using one-way ANOVA and Duncan's Multiple Range Test (DMRT). Results: The hedonic test showed no significant differences (p-value>0.05) between the sensory attributes of export and national tempe but had significantly better hedonic quality attributes (p-value<0.05) than local tempe, particularly in texture, color, appearance, and overall attributes. The CATA result indicated that the sensory attributes that should be present in fresh tempe include white color (p-value<0.001) and beany aroma (p-value<0.05). Conclusions: Export and national scale tempe showed the same level of acceptance, and both were significantly better (p-value<0.05) than local tempe in the attributes of color, appearance, and overall. In addition, export and national scale tempe had significantly higher scores for the attributes of alcoholic (p-value<0.001), beany aroma (p-value<0.05), brown-ebony (p-value<0.001), white color (p-value<0.001), yellow color (p-value<0.05), hard texture (p-value<0.05), and brittle texture (p-value<0.05).